Study on synergistic effect of multiple physical fields on hot mix asphalt during compaction process - Huanan Yu; Yutang Gao; Guoping Qian; Chao Zhang; Changyun Shi; Jinguo Ge; Wan Dai (Mathematical Biosciences and Engineering, 2024)
The multiple physical fields of hot mix asphalt (HMA) during the compaction process have a significant impact on the durability of asphalt pavement, and this research aimed to evaluate the synergistic effect of the HMA field compaction of multi-physical field evolution during the compaction process. First, the temperature field, structural layer thickness variation, and structural layer density variation were monitored during field compaction. Second, the evolution properties of compaction thickness were obtained under the synergistic influence of multi-physical fields by temperature field and compaction thickness. Finally, the evolution properties of compaction density were obtained under the synergistic influence of multi-physical fields based on the temperature field and structural layer density. The results showed that the field compaction process could be characterized by three stages under the synergistic impact of multi-physical fields. The cooling of the temperature field presents two-stage characteristics. There were cubic polynomial evolution properties for the temperature field versus time and the density versus temperature field. There was an exponential relationship between the thickness of the compacted layer and the number of mills. The aggregate particles showed different motion characteristics in the horizontal and vertical directions and vertical directions. The vertical displacement was larger than the horizontal displacement under the synergistic influence of multi-physical fields during the three stages of compaction. The migration and reorganization of aggregate particles affected the evolution of the multi-physics fields of the compaction process under the action of different compaction modes.